Sequencing the exon 1 of MSTN in Mongolian horse (Equus caballus) (Mongolian Journal of Agricultural Sciences, 2019)
Myostatin (MSTN) is a protein responsible for muscular tissue differentiation, development, and growth in mammals. Studies on cattle, mice, pig, and dog have provided sample demonstrations of mutations on myostatin, which strongly affected animal Ankole93200phenotype, particularly muscle development. In horse, myostatin gene is usually studied with respect to racing performance. Most Mongolian native horses do race for long distance and such racing is a very popular sport in Mongolia. On the other hand, the MSTN gene also affects meat yield and quality. We partially sequenced of MSTN gene to explore its polymorphic features in Mongolian horse. A 238 bp long segment of exon 1 was sequenced, using 3130 Genetic Analyser and MEGAX. The sequence was registered with accession number LC216412 in the Gene bank database of NCBI and aligned to four reference sequences (GQ183900.1, KC708233.1, AY840554.2, NM 001081817) from this database. The nucleotide diversity was 0.0084, Tajima test statistic was -1.12. so that there were 233 invariable (monomorphic) sites and 5 variable (polymorphic) sites, in the group of animals compared. The Mongolian horse differed from the reference sequence at 3 sites. There was an amino acid difference in the partial sequence, in which isoleucine in the reference sequence was converted into valine. The results of the study indicate that the Mongolian horse seems to differ substantially from the reference genome of equus caballus. Sequencing of the full length of exon 1 or even the whole MSTN gene, including introns, is strongly advised, to get more insights with regard to the identification and characterization of variants at the myostatin locus in Mongolian horses.